Computational Thinking pada Siswa Madrasah Tsanawiyah Maulana Maghribi Kandeman dalam Meningkatkan Kemampuan Pemecahan Masalah - Muhammad Nur Fain Syamsy; Alimatus Sholikhah (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
Mathematics learning in every era always provides the latest changes and revisions. This is done so that students are more interested in learning mathematics and it is hoped that this interest can improve student learning outcomes in mathematics. Computational Thinking is a method or concept of problem solving through the concept of computational thinking. Problem solving is an important asset that Indonesian children must have for creative and innovative competition in the future. While Bebras Task has an important role for students to encourage creativity and innovation in computational thinking. This study aims to improve math problem solving skills through computational thinking. Data collection techniques were carried out with tests, questionnaires, observation, documentation, and interviews. This research method is quantitative research, with quantitative data analysis techniques using the t test. the results of this study are an increase in creativity and thinking skills in problem solving skills through computational concepts.